Livestock-Associated Methicillin Resistant Staphylococcus aureus (LA-MRSA) Clonal Complex (CC) 398 Isolated from UK Animals belong to European Lineages - Sharma, Meenaxi; Nunez-Garcia, Javier; Kearns, Angela M.; Doumith, Michel; Butaye, Patrick R.; Argudín, M. Angeles; Lahuerta-Marin, Angela; Pichon, Bruno; AbuOun, Manal; Rogers, Jon; Ellis, Richard J.; Teale, Christopher; et al. (Frontiers in Microbiology, 2016)
In recent years, there has been an increase in the number of livestock-associated methicillin resistant Staphylococcus aureus (LA-MRSA) clonal complex (CC) 398 recovered from S. aureus isolated animals in the UK. To determine possible origins of 12 LA-MRSA CC398 isolates collected after screening more than a thousand S. aureus animal isolates from the UK between 2013- 2015, , whole genome sequences (WGS) of CC398 European, including UK, and non-European isolates from diverse animal hosts were compared. Phylogenetic reconstruction applied to WGS data to assess genetic relatedness of all 89 isolates, clustered the 12 UK CC398 LA-MRSA within the European sub-lineages, although on different nodes; implicating multiple independent incursions into the UK, as opposed to a single introduction followed by clonal expansion. Three UK isolates from healthy pigs and one from turkey clustered within the cassette chromosome recombinases (ccr)C S. aureus protein A (spa)-type t011 European sub-lineage and three UK isolates from horses within the ccrA2B2 t011 European sub-lineage. The remaining UK isolates, mostly from pigs, clustered within the t034 European lineage. Presence of virulence, antimicrobial (AMR), heavy metal (HMR), and disinfectant (DR) resistance genes were determined using an in-house pipeline. Most, including UK isolates, harboured resistance genes to ≥3 antimicrobial classes in addition to β-lactams. HMR genes were detected in most European ccrC positive isolates, with >80% harbouring czrC, encoding zinc and cadmium resistance; in contrast ~60% ccrC isolates within non-European lineages and 6% ccrA2B2 isolates showed this characteristic. The UK turkey MRSA isolate did not harbour φAVβ avian prophage genes (SAAV_2008 and SAAV_2009) present in US MSSA isolates from turkey and pigs. Absence of some of the major human-associated MRSA toxigenic and virulence genes in the UK LA-MRSA animal isolates was not unexpected. Therefore, we can conclude that the 12 UK LA-MRSA isolates collected in the past two years most likely represent separate incursions into the UK from other European countries. The presence of zinc and cadmium resistance in all nine food animal isolates (pig and poultry), which was absent from the 3 horse isolates may suggest heavy metal use/exposure has a possible role in selection of some MRSA.